The Level of Internet Adoption in Business Reporting: The Nigerian Perspectives - Hussain Salaudeen; Sunday Adebayo Alayemi (Politeknik Negeri Bandung, 2020)
In recent years, a paradigm shift has occurred regarding the way firms report their activities. Instead of using the traditional approach, otherwise called paper-based reporting, the trend has switched into the use of a more sophisticated approach referred to as internet or web-based reporting. This study examines the extent of internet implementation in business reporting by emphasizing on the listed manufacturing companies in Nigeria. For the purpose of this study, all manufacturing companies listed on the Nigerian Stock Exchange constitute the population. The purposive sampling procedure was employed to select forty-five out of ninety listed companies. Primary data were obtained from a thematic questionnaire that uses validated scales. The data collected were analyzed using both descriptive and inferential statistics. Specifically, Principal Component Analysis (PCA) was the inferential statistic used to evaluate the extent to which manufacturing companies employ the internet in reporting their financial and non-financial activities. The results show that the listed manufacturing companies are at the exploratory stage. The internet is employed either as an extension activity or enrichment exercise to the hard copy business reporting model. This study offers a guide to stakeholders of the listed manufacturing companies to enhance their competitive advantage by employing technology in reporting their activities.